Distinction between nominal compounds and nominal phrases - Chen, Xiaoming (The University of Edinburgh, 2012)
Compounding in English is a rather complex word-formation process and it is intensively discussed in the linguistic literature. However, there remain several unsolved problems: the definition of ‘compound’, the classifications of compounds and the distinction between compound nouns and noun phrases. The present paper will address the first two problems first and then it will focus on the main problem: the distinction between noun compounds and noun phrases. The linguists do not provide a consistent definition of the term ‘compound’ and they also do not provide a coherent classification of compounds. The aim of the present paper is to discuss the dividing borderline between nominal compounds and nominal phrases. As to the distinction between these two constructions, the paper mainly explores three criteria: phonological criteria, syntactic criteria and semantic criteria. As can be seen below, all these three criteria are not reliable and satisfying enough to draw a clear borderline between compound nouns and nominal phrases, but they are applicable and relevant and to some degree.
Keywords: Nominal compounds; Nominal phrases; Phonological criteria; Syntactic criteria; Semantic criteria